2022
DOI: 10.1186/s11658-022-00307-x
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy biochemical characterisation of bladder cancer cisplatin resistance regulated by FDFT1: a review

Abstract: Bladder cancer is the fourth most common malignancy in males. It can present across the whole continuum of severity, from mild through well-differentiated disease to extremely malignant tumours with poor survival rates. As with other vital organ malignancies, proper clinical management involves accurate diagnosis and staging. Chemotherapy consisting of a cisplatin-based regimen is the mainstay in the management of muscle-invasive bladder cancers. Control via cisplatin-based chemotherapy is threatened by the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 100 publications
0
15
0
Order By: Relevance
“…Kanmalar et al conducted a review on bladder cancer comparing previous work that applied RS on tissue, blood, serum, and urine. 147 The study focused on the classification of chemosensitivity status based on Raman features associated with cholesterol metabolism. They identified farnesyl-diphosphate farnesyltransferase 1 (FDFT1) expression and its effect on cholesterol biosynthesis as a potential driver of cholesterol-linked chemoresistance.…”
Section: Metabolism In Cancermentioning
confidence: 99%
“…Kanmalar et al conducted a review on bladder cancer comparing previous work that applied RS on tissue, blood, serum, and urine. 147 The study focused on the classification of chemosensitivity status based on Raman features associated with cholesterol metabolism. They identified farnesyl-diphosphate farnesyltransferase 1 (FDFT1) expression and its effect on cholesterol biosynthesis as a potential driver of cholesterol-linked chemoresistance.…”
Section: Metabolism In Cancermentioning
confidence: 99%
“…This limitation has resulted in the unnecessary exposure of successfully cured patients to the toxicity of adjuvant therapy, whereas others with residual disease may not receive potentially beneficial treatment until disease progression can be detected by imaging. A comprehensive understanding of the subgroup of patients predicted to become resistant to cisplatin is essential for patient treatment modalities [ 18 ]. The advent of immunotherapy, especially immune checkpoint inhibitors (ICIs), has revolutionized the landscape of BC systemic therapy over the past 5 years.…”
Section: Introductionmentioning
confidence: 99%
“…Sensitive and precise detection of chemical changes in biomolecules due to development of cancers is possible using vibrational spectroscopy methods, namely infrared (IR) absorption, 9 Raman spectroscopy, 10 12 and surface-enhanced Raman scattering (SERS) spectroscopy. 13 16 It has been previously shown that both of these methods can be used to discriminate between the cancerous and normal tissues or cells of various cancers, like brain, 17 20 breast, 21 24 or others.…”
Section: Introductionmentioning
confidence: 99%
“…Sensitive and precise detection of chemical changes in biomolecules due to development of cancers is possible using vibrational spectroscopy methods, namely infrared (IR) absorption, Raman spectroscopy, and surface-enhanced Raman scattering (SERS) spectroscopy. It has been previously shown that both of these methods can be used to discriminate between the cancerous and normal tissues or cells of various cancers, like brain, breast, or others. Similarly, we have showed that SERS and attenuated total reflectance Fourier-transform infrared (ATR-FTIR) methods can be used to detect kidney cancer through the analysis of the extracellular fluid. , Nowadays, a lot of research has been focused to nondirect cancer detection through “liquid biopsies” since this method can be potentially noninvasive. A number of vibrational spectroscopy studies have been performed regarding bladder cancer as well. It has been shown that FTIR spectroscopy can be used not only to distinguish cancerous and normal bladder tissues , but also to detect bladder cancer from bladder washings . Raman spectroscopy possesses several advantages comparing with other spectroscopy methods, such as (i) negligible interference from water, (ii) rich vibrational information on bonding and interactions of molecular groups, (iii) narrow vibrational bands, and (iv) resonance and surface enhancement possibilities.…”
Section: Introductionmentioning
confidence: 99%